Unemployed, Now What? The Effect of Immigration on Unemployment Transitions of Native-born Workers in the United States (2016)
Although one would expect the unemployed to be the population most likely affected by immigration, most of the studies have concentrated on investigating the effects immigration has on the employed population. Little is known of the effects of immigration on labor market transitions out of unemployment. Using the basic monthly Current Population Survey from 2001 and 2013 we match data for individuals who were interviewed in two consecutive months and identify workers who transition out of unemployment. We employ a multinomial model to examine the effects of immigration on the transition out of unemployment, using state-level immigration statistics. The results suggest that immigration does not affect the probabilities of native-born workers finding a job. Instead, we find that immigration is associated with smaller probabilities of remaining unemployed, but it is also associated with higher probabilities of workers leaving the labor force. This effect impacts mostly young and less educated people.